The Problem(s) of Reading 1 Peter after Supersessionism - Kelly D. Liebengood (Religions, 2023)
Recently, there has been a growing interest in the creative identity formation strategies found in 1 Peter, especially concerning the way that the letter appropriates the Jewish scriptures and Israel’s privileges, promises, and vocation. While some find these strategies to be beneficial, others regard them as problematic because they promote a posture of supersessionism toward Israel. Some have suggested that the problem of supersessionism can be ameliorated by noting the silence in the letter regarding the relationship between Israel and the gentile addressees. This silence creates theological and hermeneutical space to go outside of the text itself to resolve the tension. But the move to go outside of the text can create its own problems because of the influential “standard canonical narrative”, which fills the silence and exerts pressure on the reader to replace Israel with the church. This article seeks to demonstrate that the text of 1 Peter itself pushes against a supposed supersessionist posture in part because such a reading is inconsistent with the claims made about God, but also because the implicit narrative in the letter along with the exhortations to distance oneself from a gentile way of life necessitate that the addressees “appropriate Israelhood” without expropriating Israel.